2015
DOI: 10.1111/1471-0307.12220
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of milk fat globule diameter, fat and cholesterol content and milk epithelial cell gene expression in dairy cows

Abstract: It was possible to show a connection between the temporal variation of milk fat globule diameter, fat and cholesterol content in milk and the expression of candidate genes in the mammary gland epithelial cells in milk. The beginning of lactation corresponded with higher levels of fat and cholesterol in the milk as a result of a higher expression of key enzymes in the purified bovine milk epithelial cells, paralleled with an increase in milk fat globule mean size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…Moreover, CHL_fat in this study had a larger range (from 102.1 mg to 549.22 mg 100 g −1 fat) compared with 204.4-382.5 mg 100 g −1 fat in German cows (n = 1142) (Precht 2001). Sample variation generally increases with increase in sample size; this study was based on a larger sample size (n = 1793) compared with previous studies (Precht 2001;Strzałkowska et al 2009a;Altenhofer et al 2015). Moreover, samples in this study originated from 29 herds and milk CHL content varied significantly (P < 0.001) among herds.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Moreover, CHL_fat in this study had a larger range (from 102.1 mg to 549.22 mg 100 g −1 fat) compared with 204.4-382.5 mg 100 g −1 fat in German cows (n = 1142) (Precht 2001). Sample variation generally increases with increase in sample size; this study was based on a larger sample size (n = 1793) compared with previous studies (Precht 2001;Strzałkowska et al 2009a;Altenhofer et al 2015). Moreover, samples in this study originated from 29 herds and milk CHL content varied significantly (P < 0.001) among herds.…”
Section: Discussioncontrasting
confidence: 45%
“…Several gene expression and proteomics studies have reported genes with potential involvement in milk CHL concentration and metabolism. (Viturro et al 2009;Mani et al 2011;Schlegel et al 2012;Ontsouka et al 2013Ontsouka et al , 2017Weber et al 2013;Kessler et al 2014;Altenhofer et al 2015;Gross et al 2015). For instance, Mani et al (2011) reported the presence of ABCA1 and ABCG1 proteins in milk fat globule membranes, thus suggesting their potential involvement in CHL exchange between mammary epithelial cells and alveolar milk.…”
Section: Introductionmentioning
confidence: 99%
“…The color of milk has been shown to vary with stage of lactation, infection (mastitis), breed, and season (Doan, 1924;McDermott et al, 2016) with numerous and smaller milk fat globules (MFG) giving rise to higher reflectance, resulting in a lighter milk. Size of MFG has been reported to be influenced by factors such as diet (Couvreur et al, 2007) and stage of lactation (Mesilati-Stahy and Argov-Argaman, 2014;Altenhofer et al, 2015). In our study, the lower values for lightness in raw milk samples during outdoor season (lower L*-value), were possibly explained by fewer or larger MFG during summer months.…”
Section: Short Communicationmentioning
confidence: 49%
“…For instance, the average MFG diameter is 0.3 µm lower in Holstein cows (3.3 µm) in comparison with Normandy cows (3.6 µm) Logan et al, 2014); in comparison with a maize silage-based diet, it decreases down to 0.3 to 0.4 µm when cows are fed on pasture (3.4 v. 3.1 µm, respectively) or on a supplemented maize silage diet with linseed oil (4.2 v. 3.8 µm, respectively) (Couvreur et al, 2006 andHurtaud et al, 2010;Lopez et al, 2014) and down to −0.2 µm with high-concentrate low-forage diets . It is modulated by the lactation stage (Mesilati-Stahy and Argov-Argaman, 2014; Altenhofer et al, 2015). On the other hand, the MFG diameter varies from 2.5 up to 5 µm between cows in the same herd .…”
Section: Introductionmentioning
confidence: 99%